Item Analysis of Multiple-Choice Questions of Mid-Semester Assessment of Mathematics in the Fifth-Grade Elementary School in Wates District Year 2021/2022 - Wahyuning Arisa Dewi; Sulis Fitri Lestari; Attar Nazaruddin Mirza; Risca Jayanti Ratmadiyah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
This research aims to determine the quality of the multiple-choice test items for the Mid-Semester Assessment of Mathematics in the fifth-grade elementary school in Wates District Year 2021/2022. The quality of the items in terms of validity, reliability, level of difficulty, and discriminating power. This study was qualitative research. The subject in this research was a teacher and 84 students in fifth-grade elementary school students in Wates District Year 2021/2022. Data was collected by documentation method. Data were analyzed using SPSS Version 25. The data analysis technique used the difficulty index analysis technique, discriminating power, validity test, and reliability test. The results show (1) Quality items based on validity and valid question amounted to about eight items or 100%; (2) Quality items based on reliability can be concluded that the test items were reliable, with a reliability rate of 0.7359; (3) Quality items based on the level of difficulty, items that were relatively difficult and the medium was 0 item and relatively easy items amounted to 8 items or 100%; (4) Quality items based on discriminating power, there was 1 item or 12,5% in the excellent category, three items or 37,5% in the good category, and four items or 50% in the poor category. Keywords: analysis items, mathematics, mid-semester assessment ===================================================== Penelitian ini bertujuan untuk mengetahui kualitas soal pilihan ganda Penilaian Tengah Semester Matematika pada siswa kelas V SD Negeri Wates Tahun Pelajaran 2021/2022. Kualitas butir soal ditinjau dari validitas, reliabilitas, tingkat kesukaran, dan daya pembeda. Penelitian ini merupakan penelitian kualitatif. Subjek dalam penelitian ini adalah guru dan 84 siswa kelas V SD Wates Tahun 2021/2022. Pengumpulan data dilakukan dengan metode dokumentasi. Data dianalisis menggunakan SPSS Versi 25. Teknik analisis data menggunakan teknik analisis indeks kesukaran, daya pembeda, uji validitas, dan uji reliabilitas. Hasil penelitian ini adalah: (1) Kualitas butir soal berdasarkan validitas, soal yang valid berjumlah 8 butir atau 100%; (2) Kualitas butir soal berdasarkan reliabilitasnya dapat disimpulkan butir soal tes reliabel, dengan tingkat reliabilitas 0,7359; (3) Kualitas butir soal berdasarkan tingkat kesukarannya, yaitu soal relatif sukar dan sedang adalah 0 dan soal relatif mudah berjumlah 8 butir atau 100%; (4) Kualitas item berdasarkan daya pembeda, terdapat 1 item atau 12,5% yang termasuk dalam kategori baik, 3 item atau 37,5% pada kategori cukup, dan 4 item atau 50% pada kategori kurang. Kata kunci: 4 C’s, learning, critical thinking, creative thinking, sekolah dasar